A comparative study of an industrial effluent treatment using enzymatic and alkaline adapted consortium assays. Issue 4 (21st June 2012) - Younes, Sonia Ben; Ellouze, Mariem; Sayadi, Sami
Abstract BACKGROUND: Dyeing effluents are the main source of water pollution from textile industries. Consequently, the treatment of such effluents is of environmental concern. RESULTS: Decolorization of a textile industry effluent was investigated using, for the first time, the trimeric Scytalidium thermophilum laccase without mediator addition. The maximum effluent decolorization (50%) was achieved after 8 h using a diluted effluent (5 fold) and 4 units of crude enzyme, operating at 50 °C and pH 4. Characterization of raw effluent presents two peaks as demonstrated by the UV‐visible spectrum, showing an intensive peak around 670 nm and a smaller one at 290 nm. At the end of the enzymatic treatment, these two peaks disappeared and a new peak emerged at 280 nm. Because laccase catalyzed effluent decolorization percentage did not exceed 50%, an alkaline adapted consortium treatment assay of this effluent was carried out. An alkaline adapted consortium was used at bench scale in order to decolorize the raw effluent. After 24 h of exposure, color and COD (chemical oxygen demand) removal rates reached 73% and 71%, respectively, at pH 11. CONCLUSION: The adapted consortium treatment of the industrial effluent is economically very interesting since the treatment is costless and can be applied at pilot or industrial scales. © 2012 Society of Chemical Industry